Development Of New Green Chitosan-Natural Rubber And Chitosan-Banana Trunk Fibres Biocomposites As Release Matrices - ., Muhammad Rahim (2017)
A new class of green biocomposites comprising of (i) acidified chitosan (CTSAC) dispersed in partially cross-linked NR matrices ( AC-d-NR) = 2.5, 5, 10, 20 and 40-phr, and (ii) banana trunk fibres (BTF) immobilized in CTSAC (BTF-i-CTSAC) were prepared and characterized by means of Fourier Transform Infrared (FT-IR) spectroscopy, Thermogravimetric Analysis (TGA), Scanning Electron Microscope (SEM) and Brunauer–Emmett–Teller (BET). Results of FT-IR and TGA analyses revealed that, in AC-d-NR, the CTSAC was not grafted but dispersed in partially crosslinked NR, and in BTF-i-CTSAC, the BTF were merely immobilized in CTSAC AC- - = 2.5, 5, 10, 20 and 40-phr) were used as slow release matrices for several pesticides and fertilizers, and BTF-i-CTSAC (BTF = 10 %) as sorbent for the removal of Cd2+ and Cr6+ from aqueous media.